Web-Based Employee Recruitment Application at PT Parastar Group Utilizing the Rapid Application Development (RAD) Method - Teddy Septria Wiguna; Winton Ginting; NM Faizah (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The research designs a web-based employee recruitment information system developed for PT. Parastar Group, by utilizing PHP and MySQL. This system offers a solution for companies to manage applicant data archiving by HRD staff more efficiently and effectively. Applicant data is stored in a MySQL database server, reducing dependence on physical filing cabinets. In addition, applicants can complete application forms and access company information and job descriptions more efficiently. This research focuses on designing an employee recruitment information system for PT. Parastar Group, using the waterfall model as a development methodology. This system is built using the PHP programming language. The result of this research is a functional web-based employee recruitment information system. This system is expected to assist the HRD division in processing data for employee archiving and orientation.